Amygdala activation and GABAergic gene expression in hippocampal sub-regions at the interplay of stress and spatial learning - Hadad-Ophir, Osnat; Albrecht, Anne; Stork, Oliver; Richter-Levin, Gal (Frontiers in Behavioral Neuroscience, 2014)
Molecular processes in GABAergic local circuit neurons critically contribute to information processing in the hippocampus and to stress-induced activation of the amygdala. In the current study, we determined expression changes in GABA-related factors induced in subregions of the dorsal hippocampus as well as in the BLA of rats 5h after spatial learning in a Morris Water maze, using laser microdissection and quantitative real-time PCR. Spatial learning resulted in highly selective pattern of changes in hippocampal subregions: gene expression levels of neuropeptide Y were reduced in the hilus of the dentate gyrus, whereas somatostatin was increased in the stratum oriens of CA3. The GABA-synthesizing enzymes GAD65 and GAD67 as well as the neuropeptide cholecystokinin were reduced in stratum oriens of CA1. In the BLA, expression of GAD65 and GAD67 were reduced compared to a handled Control group. These expression patterns were further compared to alterations in a group of rats that have been exposed to the water maze but were not provided with an invisible escape platform. In this Water Exposure group, no expression changes were observed in any of the hippocampal subregions, but a differential regulation of all selected target genes was evident in the BLA. These findings suggest that expression changes of GABAergic factors in the hippocampus are associated with spatial learning, while additional stress effects modulate expression alterations in the BLA. Indeed, while in both experimental groups plasma corticosterone levels were enhanced, only Water Exposure stress activated the basolateral amygdala, as indicated by increased levels of phosphorylated ERK1/2. Altered GABAergic function in the BLA may thus contribute to memory consolidation in the hippocampus, in relation to levels of stress and emotionality associated with the experience.